Hypertension in Women: Should There be a Sex-specific Threshold? - Eva Gerdts (Radcliffe Medical Media, 2021)
Conventionally, hypertension is defined by the same blood pressure (BP) threshold (systolic BP ≥140 and/or diastolic BP ≥90 mmHg) in both women and men. Several studies have documented that women with hypertension are more prone to develop BP-associated organ damage and that high BP is a stronger risk factor for cardiovascular disease (CVD) in women than men. While healthy young women have lower BP than men, a steeper increase in BP is found in women from the third decade of life. Studies have documented that the BP-attributable risk for acute coronary syndromes (ACS), heart failure and AF increases at a lower level of BP in women than in men. Even high normal BP (130–139/80–89 mmHg) is associated with an up to twofold higher risk of ACS during midlife in women, but not in men. Whether sex-specific thresholds for definition of hypertension would improve CVD risk detection should be considered in future guidelines for hypertension management and CVD prevention.